2020
DOI: 10.4081/monaldi.2020.1126
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in non-anemic chronic obstructive pulmonary disease in a predominantly male population: an ignored entity

Abstract: Non-anemic iron deficiency has been studied in heart failure, but studies are lacking in chronic obstructive pulmonary disease (COPD). The potential clinical implications of association of iron deficiency with the severity of COPD warrant research in this direction. This was an observational, cross-sectional study on patients with COPD to compare disease severity, functional status and quality of life in non-anemic patients with COPD between two groups - iron deficient and non-iron deficient. Stable non-anemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Iron deficiency in COPD patients was associated with reduced exercise tolerance and increased exacerbation frequency, though it is unclear whether the effects were associated with dietary intake or microbiome composition 233 . Finally, remodelling of the airway epithelium in COPD patients contributes to the dysregulation of PUFA metabolism in the lung 234 .…”
Section: Dysbiosis Of Gut Microbiome In Diet‐related Immune Disordersmentioning
confidence: 99%
“…Iron deficiency in COPD patients was associated with reduced exercise tolerance and increased exacerbation frequency, though it is unclear whether the effects were associated with dietary intake or microbiome composition 233 . Finally, remodelling of the airway epithelium in COPD patients contributes to the dysregulation of PUFA metabolism in the lung 234 .…”
Section: Dysbiosis Of Gut Microbiome In Diet‐related Immune Disordersmentioning
confidence: 99%
“…It has been estimated that iron deficiency may take place in approximately 40–50% of the COPD patients [ 3 , 4 , 5 ]. Alterations in iron homeostasis may negatively impact disease progression and functional status in COPD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that patients with COPD have lower dietary intake of calcium, phosphorus, and iron compared with that of healthy control subjects, 124 and patients with COPD with iron deficiency have less exercise capacity, more frequent exacerbations, and increased COPD severity than do patients with COPD who do not have iron deficiency. 125 , 126 Whether low mineral status also affects lung function and COPD risk remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%